Faith and revivalism in a nordic Romani community: Pentecostalism amongst the Kaale Roma of Sweden and Finland - Thurfjell, David (Library of modern religion, 2013)
"A Pentecostal revival is sweeping the Romani communities of Europe. The dominant religious orientation of European Roma, Pentecostalism has become one of the major factors behind Romani social development, in the wake of the discrimination, marginalisation, and growing anti-ziganist sentiments of the latest decades. Through this form of charismatic Protestant Christianity, Roma have overcome social problems and internal conflicts as well as battle against the hostility and exclusion of the 'macro gajo' (non-Roma) society. Based on interviews and field work, this original ethnographic study offers a unique presentation and analysis of the Pentecostal revival in one of Europe's many Romani communities - the Kaale Roma of Finland and Sweden. Through individual life stories, historical exposes, sociological interpretation, and ritual and discourse analysis, Thurfjell provides a vivid, accurate portrait of the multifaceted and complex situation of contemporary Roma. Despite the efforts of the Nordic welfare state over the past decades to counteract poverty, and to integrate their Romani communities into society, these groups are persistently problematic. Inspired by postcolonial theory, Thurfjell's study addresses the failure of the integration politics of the Roma; he highlights the discursive pressure the hegemonial society places on outsiders as it reaches out to help them. Romani individuals, it is argued, are caught in a deadlock between the pressure to assimilate themselves into the majority society, and that of their community, to remain Romani. This study of the Pentecostal movement is of interest to anyone who seeks to understand the religious, historical, social and discursive processes that underlie the complex and difficult situation of European Roma today."--Publisher's website